2021
DOI: 10.1103/physrevb.103.155201
|View full text |Cite
|
Sign up to set email alerts
|

Quantum transport properties of β-Bi4I4 near and well beyond the extreme quantum limit

Abstract: We have investigated the magneto-transport properties of β-Bi4I4 bulk crystal, which was recently theoretically proposed and experimentally demonstrated to be a topological insulator. At low temperature T and magnetic field B, a series of Shubnikov-De Haas(SdH) oscillations are observed on the magnetoresistivity (MR). The detailed analysis reveals a light cyclotron mass of 0.1 me, and the field angle dependence of MR reveals that the SdH oscillations originate from a convex Fermi surface. In the extreme quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…29 Beyond their suitability as model phases for bottom-up growth of complex and dimensionally-resolved q-1D vdW nanostructures, bismuth halide crystals are of particular interest due to recent studies that experimentally demonstrated both weak and higher-order topological insulating (HOTI) behavior in these crystals. 21,[30][31][32][33][34][35][36] In these studies, the topological nature of bismuth halide phases has been shown to strictly originate from the precise orientation and stacking of the q-1D [Bi 4 X 4 ] n subunits in the bulk crystal and its exposed facets. This, among the many emergent 1D/q-1D vdW crystals with size-, dimensionality-, and orientation-dependent properties, further warrants the need to understand the growth principles that underpin the controlled crystallization of well-dened 1D/q-1D vdW nanocrystals from bottom-up routes.…”
Section: Introductionmentioning
confidence: 99%
“…29 Beyond their suitability as model phases for bottom-up growth of complex and dimensionally-resolved q-1D vdW nanostructures, bismuth halide crystals are of particular interest due to recent studies that experimentally demonstrated both weak and higher-order topological insulating (HOTI) behavior in these crystals. 21,[30][31][32][33][34][35][36] In these studies, the topological nature of bismuth halide phases has been shown to strictly originate from the precise orientation and stacking of the q-1D [Bi 4 X 4 ] n subunits in the bulk crystal and its exposed facets. This, among the many emergent 1D/q-1D vdW crystals with size-, dimensionality-, and orientation-dependent properties, further warrants the need to understand the growth principles that underpin the controlled crystallization of well-dened 1D/q-1D vdW nanocrystals from bottom-up routes.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field leads to the accumulation of charges along the transverse direction of the current, where the Hall resistance provides the information on the charge carrier density and mobility. [16,17] An intrinsic mag-netic moment in the magnetic materials can give rise to a Hall signal deviating from linear behavior due to the interplay of the magnetic moment and external magnetic field, i.e., anomalous Hall effect. [18][19][20] Furthermore, the spin-orbit coupling (SOC) strength plays the crucial role in the (inverse) spin Hall effect, resulting in the accumulation of spin polarization in the transverse direction.…”
Section: Introductionmentioning
confidence: 99%